Determination of levels of visual perception of the main types of forms of art objects - Pylypchuk, Oksana; Polubok, Andrii (Landscape Architecture and Art, 2024)
This article is a study of the main forms of art objects in the interior, where a system of levels of their visual perception is proposed for the first time. Such a system represents an effective way of solving practical issues, when at the first stage of design, the artist and designer solve the problems of the place of installation of this or that art object from the point of view of determining the necessary zone of its perception depending on the type of form. The main key emphasis in the research was made on the analysis of contemplation and perception of art objects of certain forms from different perspectives. 3D modeling of conventional art objects in virtual space was used as an experimental tool. The results of various experiments with three main types of forms were presented in the form of graphic drawings, diagrams with angular dimensions of perception zones, which reflect the content and structure of the studied problems. The method of systematization and generalization of the results made it possible to formulate the necessary levels of visual perception of the main forms of art objects in the interior, which consist of: First maximum level; Second intermediate level; The third minimum level. To test the reliability, the obtained research results were checked by student design practice. The research results were applied in real architectural projects, which made it possible to evaluate their effectiveness and practical value. The effectiveness of the formulated levels of visual perception of the main types of forms of art objects in the interior space was clearly demonstrated by the results of practical implementation. The results of the research can improve the theoretical basis in the design methodology and be recommended for implementation in the educational process, as well as for practical use in the development of art objects in various types of interiors. The proposed system of levels of visual perception can allow to expand the designer’s toolkit and will contribute to the optimization of design solutions in the context of modern trends in the design of the object-spatial environment.